Implementation of YouTube and TikTok-Based Digital Literacy in Islamic Education Learning at SMKN 2 Tanjung Raya - Mawadatul Af'idati; Siti Roudhotul Jannah; Choirudin Choirudin; Subandi Subandi (CV. Bimbingan Belajar Assyfa, 2026)
This research is motivated by the challenges of Islamic Education (PAI) learning in the digital era, where conventional methods are considered less effective in reaching Generation Z students who are familiar with digital platforms. The study aims to analyze the implementation of YouTube and TikTok-based digital literacy in PAI learning at SMKN 2 Tanjung Raya, covering planning, implementation, and evaluation. A qualitative method with a case study approach was employed. Informants were determined through purposive sampling, consisting of PAI teachers, students, and the vice principal of curriculum. Data collection used observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman model (reduction, display, conclusion), with validity checks through source triangulation, technique triangulation, and member checking. The results showed: (1) Planning includes selecting relevant, accurate, and morally valuable video content; (2) Implementation is conducted interactively and multimodally by showing videos as initial stimuli, followed by discussion and reflection; (3) Evaluation covers cognitive, affective, and psychomotor aspects, including social media ethics. This implementation increased learning motivation, made abstract material more contextual, and made students more selective and responsible in consuming digital content. In conclusion, systematically managed use of YouTube and TikTok is proven effective as an adaptive pedagogical strategy in the digital era. This study recommends strengthening digital infrastructure and digital literacy training for teachers.